Apocynin Dietary Supplementation Delays Mouse Ovarian Ageing. (20th October 2019) - Timóteo-Ferreira, F.; Mendes, S.; Rocha, N. A.; Matos, L.; Rodrigues, A. R.; Almeida, H.; Silva, E.
Abstract : Advanced maternal age is associated with higher infertility rates, pregnancy-associated complications, and progeny health issues. The ovary is considered the main responsible for these consequences due to a continuous decay in follicle number and oocyte quality. Intracellular imbalance between oxidant molecules and antioxidant mechanisms, in favour of the former, results in oxidative stress (OS) that is believed to contribute to ovarian ageing. This work is aimed at evaluating whether an age-related increase in ovarian OS, inflammation, and fibrosis may contribute to tissue dysfunction and whether specific antioxidant supplementation with a NADPH oxidase inhibitor (apocynin) could ameliorate them. Mice aged 8–12 weeks (reproductively young) or 38-42 weeks (reproductively aged) were employed. Aged mice were divided into two groups, with one receiving apocynin (5 mM) in the drinking water, for 7 weeks, upon which animals were sacrificed and their ovaries collected. Ovarian structure was similar at both ages, but the ovaries from reproductively aged mice exhibited lipofuscin deposition, enhanced fibrosis, and a significant age-related reduction in primordial and primary follicle number when compared to younger animals. Protein carbonylation and nitration, and markers of OS were significantly increased with age. Moreover, mRNA levels of inflammation markers, collagens, metalloproteinases (MMPs), and tissue inhibitor MMPs (TIMPs) were upregulated. Expression of the antifibrotic miRNA29c-3p was significantly reduced. Apocynin supplementation ameliorated most of the age-related observed changes, sometimes to values similar to those observed in young females. These findings indicate that there is an age-related increase in OS that plays an important role in enhancing inflammation and collagen deposition, contributing to a decline in female fertility. Apocynin supplementation suggests that the imbalance can be ameliorated and thus delay ovarian ageing harmful effects.